Macrofaunal colonisation of stranded Durvillaea antarctica on a southern New Zealand exposed sandy beach - C Dufour; PK Probert; C Savage (New Zealand Journal of Marine and Freshwater Research, 2012)
Samples of the kelp Durvillaea antarctica were placed in mesh bags on the upper shore of a southern New Zealand exposed sandy beach and monitored over 30 days to examine their decomposition and macrofaunal colonisation. Amphipoda, Staphylinidae, other Coleoptera and Diptera made up 99.9% of total macrofaunal abundance and biomass of the colonising fauna. Amphipoda and Staphylinidae abundance differed significantly between days of exposure. All main taxonomic groups, except other Coleoptera, differed in biomass between days of exposure and between seasons, with greater biomass in autumn than winter. Decomposition rate and moisture content of D . antarctica differed significantly between days of exposure and between seasons, whereas carbon content only differed significantly over time. Correlations between macrofaunal abundance and the decomposition rate, and total macrofaunal abundance and the C:N ratio, suggest that the macrofaunal community prefers older wrack, despite it being lower in nitrogen content then fresh kelp.